Experimental Study on the Mechanical Properties and Microstructures of Cenosphere Concrete - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The most valuable components of coal fly ash are cenospheres. Cenospheres are hollow spherical particles produced during the coal-burning processes. As a result of their excellent characteristics, such as high workability, high heat resistance, low bulk density, and high strength, cenospheres can be used in the manufacturing of lightweight cement concrete. The research efforts and outcomes are to produce long-lasting cement-based lightweight concrete (LWC) composites with good mechanical properties. The novelty of this investigation is to determine the cement concrete strength when silica fume (SF) and cenospheres (CS) were used as a replacement for cement. Throughout the experiments, a consistent substitution of 12% silica fume was incorporated into cement mass. Silica is used as a micro filler and pozzolanic reactant to strengthen concrete. The concrete mixtures were tested to ensure they met the requirements of the lightweight concrete in terms of their mechanical, physical, and durability qualities. According to the findings, lightweight concrete standards were met, and environmental sustainability was improved with the use of these mix proportions. Concrete specimen’s self-weight decreases by 35% with 30% cenosphere as a replacement. The micrograph shows the lack of portlandite is filled by mullite and other alumino silicates from the cenosphere. In order to achieve sustainability in concrete manufacturing, these mixtures can be suggested for the making of structural LWC that makes use of a large volume of industrial waste while conserving cement and natural resources. © 2023 by the authors.